Blade dynamic strain non-intrusive measurement using L1/2-norm regularization and transmissibility. (28th February 2022) - Ao, Chunyan; Qiao, Baijie; Chen, Lei; Xu, Jinghui; Liu, Meiru; Chen, Xuefeng
Highlights: Dynamic strain measurement of rotating blades is conducted via Blade-Tip Timing. Blade vibration parameters are identified based on L1/2 -norm regularization. Blade dynamic strain is reconstructed based on displacement and transmissibility. The reconstructed results are compared with the strain gauges' measurements. Numerical cases and a rotor test validate the strain reconstruction method. Abstract: Dynamic strain measurement is critical in blade vibration monitoring for evaluating the residual life and health condition of rotating blades. Blade tip time (BTT) is recognized as a promising technique to replace traditional strain gauge measurement. This paper presents a method for dynamic strain reconstruction as well as vibration parameter identification based on BTT via the L1/2 -norm sparse regularization and response transmissibility. First, a sparse representation model based on the L1/2 -norm penalty is developed to identify blade vibration frequency and blade-tip displacement. Second, a displacement-to-strain transmissibility (DST) is proposed for strain reconstruction from identified displacement. The mode shapes of the blade are needed to calculate the DST. The proposed method is named L1/2 -DST, which has a great advantage of achieving non-intrusive strain measurement for rotating blades using BTT. Numerical simulation and spin experiment show that the L1/2 -DST method enables accurate dynamic strain reconstruction and robustness to noise.